Indonesian Legal Efforts in Ensuring the Protection of Victims of Child Trafficking in Indonesia - Derry Angling Kesuma (IHSA Institute, 2021)
Child protection, as defined in Law No. 11 of 2012, cannot be divorced from the legal protection principle. Both were established in international legal documents and domestic law prior to the enactment of this law. This is a qualitative study employing a normative-descriptive method to legal analysis. Secondary data was gathered using the literature review approach by comparing current legal regulations and implementing these rules in the field to ascertain the meaning of the terminology used in the legislation. As a result of this research, it is clear that protecting victims of human trafficking might take the shape of abstract (indirect) or concrete protection (direct). Abstract Protection is a type of protection that can only be experienced or felt emotionally (psychologically), such as a sense of fulfillment (satisfaction). Meanwhile, concrete protection is a type of protection that provides tangible benefits, such as material or non-material presents.